Towers of the East and Temple Compound from Lakes of the Nations, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
Looking across the Lakes of the Nations, are the great gold murals on the walls encircling the Court of the Flowers. The space between the lake and the walls is called the Temple Compound. The Towers of the East command a view of the Court and the Lake.